DUKUNGAN SUAMI PADA IBU HAMIL DALAM MENGONSUMSI TABLET FE DI WILAYAH KERJA PUSKESMAS GODEAN II SLEMAN YOGYAKARTA - Puspitasari, Dian; Maelani, Dwi (MEDIA ILMU KESEHATAN, 2018)
Background: The death rate of mother is one of indicator in society welfare to appreciate health mother efforts. Based on WHO, the number of death mother about 40% in developed country related to anemia because of iron substance deficiency. One of the component to serve pregnant woman’s health is to avoid anemia by giving 90 tablets (Fe3) of iron substance. One of psychology factor in pregnant woman which influence mother’s pregnant to consume tablet Fe is their husband’s support. Objective: To understand husband’s support for pregnant woman to consume tablet Fe in Godean II Public health Sleman Yogyakarta. Methods: This research is quantitative description. The technique of sampling uses Total Sampling technique with 43 participants. To collect data uses close questioner and data analysis uses univariat analysis. Results: The husband support for mother’s pregnant to consume tablet Fe include some categories, there are: 22 (51,2%) participants are unsupported, most of instrumental support is unsupported which are 22 (51,2%) participants, most of informational support is unsupported which are 24 (55,8%) participants, most of valuation support is supported which are 26 (60,5%) participants, and most of emotional support is supported which are 27 (62,8%) participants. Conclusion: We can conclude that husband support for mother’s pregnant to consume Fe tablet in Godean II Sleman clinic of Yogyakarta is included in unsupported category which are 22 (51,2%) participants. Keywords: Husband Support, Pregnancy, Tablet Fe